The protein architecture and allosteric landscape of HNF4α - Rastinejad, Fraydoon (Frontiers in Endocrinology, 2023)
Hepatocyte nuclear factor 4 alpha (HNF4α) is a multi-faceted nuclear receptor responsible for governing the development and proper functioning of liver and pancreatic islet cells. Its transcriptional functions encompass the regulation of vital metabolic processes including cholesterol and fatty acid metabolism, and glucose sensing and control. Various genetic mutations and alterations in HNF4α are associated with diabetes, metabolic disorders, and cancers. From a structural perspective, HNF4α is one of the most comprehensively understood nuclear receptors due to its crystallographically observed architecture revealing interconnected DNA binding domains (DBDs) and ligand binding domains (LBDs). This review discusses key properties of HNF4α, including its mode of homodimerization, its binding to fatty acid ligands, the importance of post-translational modifications, and the mechanistic basis for allosteric functions. The surfaces linking HNF4α's DBDs and LBDs create a convergence zone that allows signals originating from any one domain to influence distant domains. The HNF4α-DNA complex serves as a prime illustration of how nuclear receptors utilize individual domains for specific functions, while also integrating these domains to create cohesive higher-order architectures that allow signal responsive functions.